2023
DOI: 10.1038/s41598-022-26832-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of pediatric inflammatory multisystem syndrome temporarily-associated with SARS-CoV-2 and Kawasaki disease

Abstract: The connection between Pediatric Inflammatory Multisystem Syndrome (PIMS) and Kawasaki Disease (KD) is not yet fully understood. Using the same national registry, clinical features and outcome of children hospitalized in Germany, and Innsbruck (Austria) were compared. Reported to the registry were 395 PIMS and 69 KD hospitalized patients. Patient age in PIMS cases was higher than in KD cases (median 7 [IQR 4–11] vs. 3 [IQR 1–4] years). A majority of both PIMS and KD patients were male and without comorbidities… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…KD is associated with CAL and long-term cardiovascular sequelae, while MIS-C presents as more intense Inflammatory Syndrome, myocardial dysfunction, and cardiogenic shock [ 124 ]. In a retrospective review of 395 MIS-C and 69 KD patients, MIS-C patients presented with gastrointestinal (80%), cardiovascular (74%), and respiratory (52%) symptoms, while KD patients presented with dermatological (99% vs. 68%) and mucosal changes (94% vs. 64%), and cervical lymph node swelling (51% vs. 34%) [ 125 ]. Additional MIS-X symptoms may derive from ongoing SARS-CoV-2 infections and differences in the age demographics for current cases.…”
Section: Discussionmentioning
confidence: 99%
“…KD is associated with CAL and long-term cardiovascular sequelae, while MIS-C presents as more intense Inflammatory Syndrome, myocardial dysfunction, and cardiogenic shock [ 124 ]. In a retrospective review of 395 MIS-C and 69 KD patients, MIS-C patients presented with gastrointestinal (80%), cardiovascular (74%), and respiratory (52%) symptoms, while KD patients presented with dermatological (99% vs. 68%) and mucosal changes (94% vs. 64%), and cervical lymph node swelling (51% vs. 34%) [ 125 ]. Additional MIS-X symptoms may derive from ongoing SARS-CoV-2 infections and differences in the age demographics for current cases.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with MIS-C show KD-related features, gastrointestinal problems, and hypotension, as did our two patients in this study. The presence of KD-related features in patients with MIS-C has received clinical attention, but the extent of organ dysfunction in patients with MIS-C is of greater importance as it directly affects the disease course and outcome [ 4 , 13 ]. In children and in adults, MIS can occur as a serious post-infectious complication of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, it has been proposed that MIS-C and KDSS have a common host immune response and are of a single disease spectrum with varying severity [ 13 ]. Regardless of whether MIS-C and KDSS are the same disease entity, at least phenotypically, MIS-C and KDSS share many overlapping features [ 3 , 4 ]. We found that the most important factor that differentiates MIS-C from KDSS is whether SARS-CoV-2 has been identified as an infectious trigger.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multisystem inflammatory syndrome in children (MIS-C) is a rare but severe postinfection reaction to SARS-CoV-2 requiring intensive care treatment in 48% of patients . The precise pathogenesis and long-term clinical impact of MIS-C remain poorly understood.…”
mentioning
confidence: 99%